Evaluation of maternal plasma platelet activating factor acetylhydrolase activity and mRNA expression in pre-eclampsia: a case control study. (4th July 2021) - Gupta, Preeti; Agarwal, Rachna; Bhaskaran, Sruthi; Garg, Seema; Mehndiratta, Mohit; Radhakrishnan, Gita; Singh, Alpana; Agarwal, Richa; Narang, Divya
Abstract: Preeclampsia (PE) remains a leading cause of maternal morbidity and mortality all over the world. However, its aetiology and pathophysiology remain elusive. Platelet activating factor (PAF) is produced in response to oxidative stress and is a potent hypotensive agent. PAF acetylhydrolase (PAF-AH) inactivates PAF and is seen to decrease in normotensive women. The role of PAF-AH in preeclampsia has been in investigational literature, so far. The few studies done have shown a positive association of elevated levels of PAF-AH with preeclampsia. However, this marker has not been studied in the Indian population to-date and such studies are needed to elucidate the pathogenesis of this condition. Our study aimed to determine the PAF-AH activity by spectrophotometric assay in maternal plasma of 73 PE patients versus 73 normotensive controls and plasma PAF-AH mRNA expression to know the aberration of PAF-AH activity at the genetic level. Relative mRNA expression was calculated by Δ DCT method and a fold change was calculated by 2 –ΔDCT. We found that the mean plasma PAF-AH activity levels among cases was significantly higher than the normotensive controls. However, the mRNA expression of the PAF-AH gene was similar between the cases and controls, as well as between severe and non-severe preeclampsia (true fold change =1). To conclude, PAF-AH appears to be increased in women with preeclampsia and hence may contribute to pathophysiology and severity. However, a larger sample size will be required to reiterate this association. Recently, PAF-AH inhibitors such as Darapladib has been tested as a therapeutic option in atherosclerosis. After studying the role of PAF-AH in the pathogenesis of PE, PAF-AH inhibitors may be used as a therapeutic tool in the future in PE. IMPACT STATEMENT: What is already known on this subject? Platelet activating factor (PAF) is produced in response to oxidative stress and is a potent hypotensive agent. PAF acetylhydrolase (PAF-AH) hydrolyses and inactivates PAF and is seen to decrease in normotensive women. The role of platelet activating factor-acetylhydrolase (PAF-AH) in preeclampsia has been investigational so far. Few studies done have shown a positive association of elevated levels of PAF-AH in preeclamptic women. What do the results of this study add? Our study aimed to determine the activity of PAF-AH in maternal plasma of PE patients versus normal pregnancy and plasma PAF-AH mRNA expression to know the aberration of PAF-AH activity at the level of the gene. We found that plasma PAF-AH activity among preeclamptics was significantly higher than in the controls with a possible role in early-onset preeclampsia (<32 weeks), in the Indian population. This marker has never been studied in this population earlier. The results of our study re-emphasised its role in the pathogenesis of preeclampsia. What are the implications of these findings for clinical practice and/or further research? Such studies are important to not only give us a greater understanding of the various pathways involved in this multifactorial dreaded condition, but can also offer us a marker for early identification of women at risk. Recently, PAF-AH inhibitors like Darapladib has been tested as a therapeutic option in atherosclerosis. After studying the role of PAF-AH in the pathogenesis of PE, PAF-AH inhibitors may be used as a therapeutic tool in the future in PE.